Effectiveness of weekly azathioprine pulse in the treatment of chronic plaque psoriasis: an open‐label study. (23rd September 2016) - Verma, P.; Verma, K. K.; Khanna, N.; Gupta, S.; Bhari, N.
Summary: Background: Azathioprine is a potent immunosuppressive drug that has been used in many immune‐mediated diseases. There are a few reports of its use in psoriasis; however, azathioprine weekly pulse doses have not been evaluated in this disease. Aim: The objective of this study was to evaluate the therapeutic effectiveness of weekly oral pulse doses of azathioprine for the treatment of chronic plaque psoriasis, and to determine the side effects of this regimen both clinically and biochemically. Methods: In this open‐label clinical trial, a 300 mg bolus dose of azathioprine was given once every week orally for 24 weeks to patients with chronic plaque psoriasis having body surface area involvement of ≥ 10% and Psoriasis Area and Severity Index (PASI) of ≥ 10. Patients were evaluated every 4 weeks for 24 weeks to determine the response to treatment and any adverse effects (AEs), and then followed up for a further period of 12 weeks to determine any relapse of the disease. Results: There were 50 patients in the study, of whom 28 (56%) completed the 24 weeks of treatment and 27 (54%) completed the 12‐week post‐treatment follow‐up. Azathioprine 300 mg weekly pulse was effective in achieving PASI 75 in 42% of patients, PASI 90 in 36% of patients and PASI 100 in 22% of patients. In five patients (10%), the therapy had to be withdrawn due to AEs. Conclusion: Weekly azathioprine pulse appears to be an effective treatment for chronic plaque psoriasis, and can be used as an alternative therapy to other available therapeutic agents.